Konflik Palestina dan Israel: Perspektif Komunikasi - Harahap, Junardi (Mediator, 2005)
A harsh incident which killed Hamas top leader, Abdul Aziz Rantisi, has escalated Middle East conflict. As had been cited from many sources, Palestinians and Israelis publicly stated strong comments and blamed each other over this incident. From communication perspective, this incident and the aftermath became an example of labeling-based-conflict. Such conflict was resulted from ideological influence, life and everyday beliefs, and also religion background. One can prevent the incidents if only such differences could be maintained and managed wisely.